2020
DOI: 10.1002/dev.22023
|View full text |Cite
|
Sign up to set email alerts
|

The moderating role of externalizing problems on the association between anxiety and the error‐related negativity in youth

Abstract: The error‐related negativity (ERN) is an event‐related potential that reflects error monitoring. Enhanced ERN indicates sensitivity to performance errors and is a correlate of anxiety disorders. In contrast, youth with externalizing problems exhibit a reduced ERN, suggesting decreased error monitoring. Anxiety and externalizing problems commonly co‐occur in youth, but no studies have tested how comorbidity might modulate the ERN. In a sample of youth (N = 46, ages 7–19) with and without anxiety disorders, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Importantly, recent work has also identified moderators as of high potential importance for explaining inconsistent results and identifying early pathways of risk (Ip et al, 2019; Suor et al, 2020). Indeed, our previous work in this sample has suggested that SES can affect the pattern of development of the ERN itself (Brooker, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, recent work has also identified moderators as of high potential importance for explaining inconsistent results and identifying early pathways of risk (Ip et al, 2019; Suor et al, 2020). Indeed, our previous work in this sample has suggested that SES can affect the pattern of development of the ERN itself (Brooker, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…That is, it may be the case that a factor that is unmeasured and not hypothesized in the current study is differentiating specific types of risk. Certainly, other work has noted a need to attend to both syndrome type and overlap of symptoms when considering how the ERN relates to anxiety problems in children (Lo et al, 2017; Suor et al, 2020). Why distinct mechanisms may be involved in the manifestation of different types of anxiety symptoms, particularly given evidence for substantial overlap this early in development, is not entirely clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many areas of neuroscience research, including ERP studies, a common approach for calculating difference scores is to subtract activity during one condition ( X , the subtrahend) from activity during another condition ( Y , the minuend; Y − X ). Another approach increasing in popularity is a residualized difference score (e.g., Crane et al., 2021; Hanna et al., 2020; Klawohn et al., 2020; Macatee et al., 2020; Meyer et al., 2017; Muir et al., 2020; Sandre et al., 2020; Schroder et al., 2020; Suor et al, in press). A residualized difference score is the difference between the actual score ( Y ) and predicted score (trueŶ) using a linear regression equation (YŶ), wherein Y scores are regressed on X .…”
Section: Introductionmentioning
confidence: 99%